The effectiveness of pharmaceutical marketing - Kappe, Eelco Roel 1984- (ERIM PhD. series research in management, 2011)
"Pharmaceutical marketing effectiveness comprises the measurement of marketing efforts of pharmaceutical firms towards doctors and patients. These firms spend billions of dollars yearly to promote their prescription drugs. This dissertation provides empirical analyses and methods to contribute to several substantial problems on pharmaceutical marketing effectiveness. Using unique data in every essay, it studies the role of the firm, sales rep and doctor in pharmaceutical marketing. The first essay evaluates the size of the sales force and the allocation of sales calls among doctors. In particular, it provides a method to gauge a yet-to-be-enacted firm-initiated policy shift. The second essay studies the effectiveness of the information content provided in sales calls. The main questions evolve around the discussion of positively biased drug information and the responsiveness of doctors to that. In the third essay, the interplay between drug sales, marketing and scientific reviews is studied in detail."--publisher.